2003
DOI: 10.1128/iai.71.3.1538-1547.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role ofPLB1in Pulmonary Inflammation and Cryptococcal Eicosanoid Production

Abstract: Cryptococcal phospholipase (PLB1) is a secreted enzyme with lysophospholipase hydrolase and lysophospholipase transacylase activities. To investigate the role of PLB1 in the evasion of host immune responses, we characterized pulmonary immune responses to the parental (H99), the plb1 mutant, and the plb1 rec reconstituted mutant strains of Cryptococcus neoformans in mice. PLB1 was required for virulence during infection acquired via the respiratory tract. Mice infected with either H99 or the plb1 rec strain gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
146
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(155 citation statements)
references
References 31 publications
7
146
1
1
Order By: Relevance
“…30, 31), enzymes involved in glucuronoxylomannan synthesis (involved in production of polysaccharide capsule; ref. 12), phospholipase B1 (involved in production of eicosanoid metabolites) (32), and urease (15,27). Undoubtedly, multiple, some as-yet-undiscovered genes, are involved in penetration of the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…30, 31), enzymes involved in glucuronoxylomannan synthesis (involved in production of polysaccharide capsule; ref. 12), phospholipase B1 (involved in production of eicosanoid metabolites) (32), and urease (15,27). Undoubtedly, multiple, some as-yet-undiscovered genes, are involved in penetration of the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with the expression of virulence factors by H99 including urease and PLB1. 8,32 These previous studies have suggested that promoting a shift to a non-protective Th2 immune response could be a mechanism of H99-induced virulence.…”
mentioning
confidence: 99%
“…This strain grows in the lungs in an uncontrolled fashion, readily disseminates into CNS, and causes 100% mortality in a variety of immunocompetent mouse strains such as C57BL/6, BALB/c, CB6129F2, and CBA/J mice. 8,13,[31][32][33] The infections with H99 were previously shown to result in upregulation of several hallmarks of Th2 immunity in the lungs. This was associated with the expression of virulence factors by H99 including urease and PLB1.…”
mentioning
confidence: 99%
“…The needle was bent and inserted into the trachea, and 30 µL PBS (containing 10 5 CFU Cryptococcus) was delivered. The skin was sutured with a cyanoacrylate adhesive, and the mice recovered with no visible trauma (Noverr et al, 2003).…”
Section: Intratracheal Inoculationmentioning
confidence: 99%